Trilogi Demografis Pendidikan Anak Usia Madrasah Ibtidaiyah (SD) - Nurhadi Nurhadi (Pendidikan Agama Islam STIT Palapa Nusantara, 2020)
Education is the most important organ in social change in a better direction, individually and in groups of people and even a country. The agenda of change is the noble ideals of human nature. This is impossible if it doesn't start early. Measures for change starting from the education of children, early childhood and childhood is a golden age, to realize gold in their lives in the future requires education, teaching and habituation in every corner of children's activities, both at home, school and in the community. Therefore a measurable and realistic theory is needed. Among the actual and relevant theories in the community are the demographic trilogy. A theory that teaches environment-based education, both the family environment (home), the educational environment (school) and the community environment. The meaning of the family environment is to educate children of childhood as the age of gold in the area of their daily living quarters. It starts from giving a good name, giving halal food, cultivating it and getting used to listening to the revelation of the Qur'an in his home. Furthermore the educational environment, children in childhood should receive education from educational institutions that can deliver to a pure human identity, which always serves the divine rabbi. For this reason, the child should get an education from the Islamic elementary school or Integrated Islamic Primary School (SDIT) which is based on the development of divine nature. While the most prominent community environment is a mosque or prayer room. So the age of children at the age of basic standards must be accustomed to attending, praying and studying in mosques or mushollah. If the demographic trilogy of education for children at the age of the madrasa is elaborated in education as old as the age of Islam, of course the purpose of Islamic education will be realized, namely to make people who have moral character.